2020
DOI: 10.1097/rti.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Appropriate Use Criteria for Coronary Computed Tomographic Angiography for Chest Pain Evaluation in a Tertiary Care Emergency Room

Abstract: Purpose: Appropriate use criteria (AUC) defines the appropriateness of imaging procedures for specific clinical scenarios to promote evidence-based utilization and improve cost-effective care. The goal of this study was to assess the diagnostic yield and downstream health care resource utilization according to the AUC categorization for coronary computed tomography angiography (CCTA) in emergency department (ED) patients presenting with chest pain. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…CCTA has rapidly become an effective method for detecting CAD over the last decade. [2][3][4] Better image quality directly leads to more accurate diagnoses and treatments, while appropriate ICM administration is an influencing factor that helps improve the image quality while helping to protect renal function, 5,6 decrease the risk of possible allergic reactions and hyperthyroidism, 7 and save costs by avoiding waste. 8 Many recent studies have shown that lower ICM administration in CCTA imaging can be achieved without sacrificing the image quality with different kinds of CT scanners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCTA has rapidly become an effective method for detecting CAD over the last decade. [2][3][4] Better image quality directly leads to more accurate diagnoses and treatments, while appropriate ICM administration is an influencing factor that helps improve the image quality while helping to protect renal function, 5,6 decrease the risk of possible allergic reactions and hyperthyroidism, 7 and save costs by avoiding waste. 8 Many recent studies have shown that lower ICM administration in CCTA imaging can be achieved without sacrificing the image quality with different kinds of CT scanners.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Heart Disease and Stroke Statistics (2022 update),1 coronary artery disease (CAD) is a common disease of the cardiovascular system, the incidence of which has been increasing year by year in the recent years, and it is being seen in the younger population. CCTA has rapidly become an effective method for detecting CAD over the last decade 2–4. Better image quality directly leads to more accurate diagnoses and treatments, while appropriate ICM administration is an influencing factor that helps improve the image quality while helping to protect renal function,5,6 decrease the risk of possible allergic reactions and hyperthyroidism,7 and save costs by avoiding waste 8…”
Section: Introductionmentioning
confidence: 99%